Debt contracts and stochastic default barrier - Martin Dózsa; Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This article presents structural asset pricing model with stochastic interest rate and default barrier based on the evolution of the firm' Earning Before Interest and Taxes (EBIT). This framework is further enhanced by the game theory analysis which examines the negotiation between shareholders and creditors with respect to the debt of the company and its safety covenants serving as the default trigger. As a result, this complex framework allows toanalyse different optimal capital structures of the company and its default probability dependent on the changes in the risk-free interest rate, which may also represent the current state of the economy. As the numerical computations show this approach is more convenient than the constant default barrier framework used in the currently available literature.
Keywords: C73; G12; G32; G33; 330; credit contracts; stochastic default barrier; asset pricing; EBIT-based models; structural models